Implementasi MDLC untuk Aplikasi Edukasi Seks Anak Berbasis Android - Tio, Ayank; Rahayu, Sri (Jurnal Algoritma, 2025)
Sex education is an important element in modern learning strategies that aim to educate children about sexual health and create informative interactions between educators and students. However, currently sex education is still widely carried out through lecture methods, which are often less interactive for children. This method can also lead to a lack of understanding and active involvement of children in learning. The lack of interactive and easily accessible media for children and parents outside the school environment is also a problem. Therefore, the purpose of this study is to design an Android-based application for sex education that can be used in schools and homes to improve children's understanding and self-protection. With this application, it is hoped that sex education can be delivered in a more interesting, interactive, and easily accessible way, both by children and parents. The methodology used is the Multimedia Development Life Cycle (MDLC) which is divided into six stages, namely starting from concept, design, material collection, development, testing, and distribution. The evaluation was carried out using alpha testing and beta testing with the blackbox testing method, which focuses on testing software functionality without paying attention to the details of its internal implementation. The results of the research are an Android-based learning media application with various features, such as materials in the form of images, music, animated videos, and educational games as a learning medium for sex education for children.